Uraemic myoclonus: an example of reticular reflex myoclonus? - Chadwick, D (1979)
Two patients are described who developed action, reflex myoclonus during acute renal failure. In both cases the myoclonus was abolished after the intravenous administration of clonazepam. We suggest that the characteristic action myoclonus, which occurs in both acute renal failure and postanoxic encephalopathy, is caused by a disturbance of function in the lower brainstem reticular formation.